2020
DOI: 10.1038/s41598-020-75797-w
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between plasma total homocysteine level and gestational diabetes mellitus in a Chinese Han population

Abstract: To assess the correlation between plasma total homocysteine (tHcy) level and gestational diabetes mellitus (GDM) in a Chinese Han population. This case–control study included 350 GDM patients and 346 gestational week-matched normal glucose tolerance (NGT) pregnant women. Plasma tHcy and insulin levels were analyzed by HPLC and ELISA respectively. Logistic regression analysis was used to investigate the correlation between plasma tHcy level and risk of GDM. Women with GDM had a higher plasma tHcy level than NGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, neither study observed differences in serum vitamin B12 nor folate. Several studies which did not stratify for glucose intolerance have also observed increased serum homocysteine in women with GDM-complicated pregnancies compared to non-GDM pregnancies [ 122 , 123 , 124 , 125 , 126 ].…”
Section: Association Between One-carbon Metabolism Players and Gdmmentioning
confidence: 99%
“…Interestingly, neither study observed differences in serum vitamin B12 nor folate. Several studies which did not stratify for glucose intolerance have also observed increased serum homocysteine in women with GDM-complicated pregnancies compared to non-GDM pregnancies [ 122 , 123 , 124 , 125 , 126 ].…”
Section: Association Between One-carbon Metabolism Players and Gdmmentioning
confidence: 99%
“…The diagnosis of GDM was based on the criteria of International Association of Diabetes and Pregnancy Study Groups. The pregnancy was judged as GDM with blood glucose levels at any time over the following criterion: fasting 5.1 mmol/L, 1 h 10.0 mmol/L and 2 h 8.5 mmol/L 10 . Finally, 120 GDM patients and 108 gestational week‐matched pregnancies with NGT were enrolled in our study.…”
Section: Methodsmentioning
confidence: 99%
“…A case-control research was conducted in China; it contained 350 GDM women and 346 normal glucose tolerance (NGT) pregnant females [ 122 ]. Patients with GDM exhibited an elevated plasma tHct expression than NGT females ( P < 0.05) [ 122 ].…”
Section: Hct and Gdmmentioning
confidence: 99%
“…A case-control research was conducted in China; it contained 350 GDM women and 346 normal glucose tolerance (NGT) pregnant females [ 122 ]. Patients with GDM exhibited an elevated plasma tHct expression than NGT females ( P < 0.05) [ 122 ]. The GDM risk was 1.79 times higher in patients with increased tHct (≥7.29 μ mol/L) relative to females with lower tHct expression (<5.75 μ mol/L) [ 122 ].…”
Section: Hct and Gdmmentioning
confidence: 99%
See 1 more Smart Citation